Penyisihan Kandungan Perak dalam Limbah Cair Pencucian Film Melalui Proses Biofiltrasi dengan Tanaman Eceng Gondok - Diyar Kholisoh, Siti; Wahyu Widayati, Tunjung; Achmad, Zubaidi; Hadi, Faizah (Jurnal Teknologi, 2024)
Wastewater produced from the film washing process in photo studios generally has very high contents of heavy metals, such as silver (Ag). This situation can cause various health and environmental problems if it is not treated before disposal. Therefore, this research was aimed to reduce the silver content in the wastewater through biological processes. This study was conducted using a biofiltration process using water hyacinth plants. Film washing waste was first acclimatized into concentration of 2.5% and the initial silver content was measured. Afterwards, water hyacinth of 600, 900, 1200, and 1500 g, respectively, was planted into the wastewater. Waste samples were subsequently taken and analyzed every 2 days. The highest removal efficiency of 99.94% was yielded for 1500 g of plant. In this condition, the silver content in wastewater met the environmental quality standards.